ANALISIS PENERAPAN TEAM GAMES TOURNAMEN (TGT) DALAM PERKEMBANGAN KEMAMPUAN MATEMATIKA SISWA KELAS 2 MI RAUDLATUL HASAN - Ika Rohmah Setiowati Ningsih; Yulina Fadilah; Nur Khosiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research investigates the application of the cooperative learning model Team Games Tournament (TGT) in strengthening the mathematical abilities of second-grade students at MI Raudlatul Hasan. A descriptive qualitative design was employed, utilizing observation, interviews, and documentation as data collection techniques. The participants consisted of 15 students and one classroom teacher who served as the primary informant. Data analysis followed the Miles and Huberman framework, involving data reduction, data presentation, and the formulation of conclusions. The results reveal that the TGT model contributes significantly to students’ cognitive growth, particularly in grasping basic operations such as addition, subtraction, and simple problem-solving procedures. Improvements were also evident in affective aspects, including increased motivation, engagement, and confidence during mathematics lessons. Furthermore, students’ psychomotor skills developed through their involvement in game-based learning activities and the use of instructional materials during tournament sessions. Overall, the implementation of TGT creates a supportive learning atmosphere that promotes collaboration, positive competition, and active participation among young learners. The study highlights the need for well-structured planning and a strong facilitative role from teachers to maximize group interaction and enhance students’ mathematical development.